Constraints of zircon U-Pb-Hf isotopes from Late Permian-Middle Triassic flora-bearing strata in the Yanbian area (NE China) on a scissor-like closure model of the Paleo-Asian Ocean. (1st October 2019) - Shen, Xiaoli; Du, Qingxiang; Han, Zuozhen; Song, Zhigang; Han, Chao; Zhong, Wenjian; Ren, Xiang
Graphical abstract: Highlights: Provenances of Permo-Triassic clastic rocks in eastern CAOB change from single to bidirectional. The mixing of the Angaran and Cathaysian floras occurred during the Late Permian-Middle Triassic. The PAO closed via a scissor-like closure model from west to east with bidirectional subduction. Abstract: The mixture of the Cathaysian and Angaran floras signifies the evolution of the Paleo-Asian Ocean (PAO). In this study, we present new zircon U-Pb-Hf isotope analyses from the Jiefangcun Formation, Sidonggou Formation, Kedao Group, and Kaishantun Formation in the Yanbian area, NE China. The Kaishantun Formation contains the Kaishantun flora, which is dominated by the Cathaysian flora with a few Angaran elements. The Jiefangcun Formation is characterized by the Jiefangcun flora, which is dominated by the Angaran taxa and contains some Cathaysian elements. The ages of these strata are widely accepted as Permian. However, in this study, the youngest zircon ages of the rock samples from the Jiefangcun Formation, Kedao Group and Sidonggou Formation are 243–245 Ma. Only the Kaishantun Formation is assigned to the Late Permian. The Kaishantun Formation has age peaks at 758, 934, 1856, and 2493 Ma with negative εHf (t) values, and this formation is therefore mainly derived from the North China Craton (NCC). In contrast, the Kedao Group and Jiefangcun Formation have zircon age peaks at 260, 338 and 460 Ma with positive and negative εHf (t) values, at 800–1000 Ma with mostly positive εHf (t) values, and at 1800 Ma with positive and negative εHf (t) values, which suggest bidirectional provenances, including the Jiamusi-Mongolia Block and the NCC. Thus, the mixing between the Angaran and Cathaysian floras occurred during the Late Permian-Middle Triassic, suggesting a scissor-like closure model of the PAO, and the Solonker suture zone extends eastward to the Yanbian area with bidirectional subduction of the PAO.